(untitled) (Research, Society and Development, 2021)
The pitaya has been attracting the attention of consumers and fruit growers in different regions of Brazil, especially due to its exotic characteristic. After exploring the pulp of the fruit, a large amount of seeds is generated that can be used for oil extraction after previous drying. Thus, the objective was to dry seeds of red pitaya (Hylocereus polyrhizus) in a convective dryer at temperatures of 50, 60 and 70 °C and dehydration air speeds of 0.55 and 0.75 m s- 1, and to adjust different models to experimental data. It was observed that the increase in the temperature and speed of the drying air promoted a reduction in dehydration times, and the process occurred in a period of decreasing water reduction rate, in all conditions evaluated. Among the models adjusted to the drying kinetics data, Page was selected as the most suitable to represent the investigated phenomenon, presenting coefficients of determination (R2) above 0.99, mean square deviations (DMQ) below 0.030 and distribution random waste.